Different lenses, different lifeways: Embracing indigenous worldviews for sustainability transformations - Lebron, Rosangel (2025)
The climate crisis and unsustainable economic practices are reinforced by colonial values like nature instrumentalism and individualism, which shape global sustainability agendas. In contrast, Indigenous values grounded in a holistic understanding have fostered communal sustainability for centuries but remain underrepresented in sustainability practice. This paper compares Indigenous worldviews alongside modern cultural worldviews. Additionally, it examines different sustainability proposals and practical examples of Indigenous principles in policy and business settings (such as urban policy or consulting firms). Results suggest that Indigenous values linked to interconnectedness foster sustainable lifestyles and community and nature protection. However, values that disrupt human-nature connections hinder sustainability transformations. Contributing to the literature gap on worldviews and sustainability, this work aims to bridge fragmented knowledge of Indigenous sustainability proposals by mapping their principles and providing practical examples to inform policy and practice. Ultimately, this study highlights the need to integrate Indigenous perspectives for genuine transformation in sustainability practices.